Pencerahan Kronologi Pameran Still (A) Live - Paiman, Noor Azizan Rahman; Mohd Aripin, Nur Adibah Nadiah; Matrahah, Izaddin (Idealogy Journal; Vol 4 No 1 (2019): Idealogy Journal (April 2019)DO - 10.24191/idealogy.v4i1.145, 2019)
Letter to Editor - No Abstract Abstrak Pandangan - tiada abstrak